Mudra Dewata Nava Saṅga: Komunikasi Non-Verbal dalam Tradisi Watukaru - Ni Made Adnyani (Jurnal Yoga dan Kesehatan, 2023)
Nonverbal communication in the form of hand gestures has been used by humans for thousands of years. Before language was developed and before the appearance of writing, hand gestures were a way of human interaction. Therefore, in historical artifacts in various civilizations and religions around the world, hand gesture is a dominant role. When choose this study, the authors focused on the form of the mudra dewata nava saṅga and its symbolic meaning as a non-verbal communication in dealing with the gods. This research on mudras as non-verbal communication in the watukaru tradition uses a qualitative descriptive approach that focuses on social phenomena, giving voice to the feelings and perceptions of the participants. The research procedure carried out produces descriptive data which includes sentences and images originating from the research object. The data analysis process used is data analysis in the field model Miles and Huberman. Activities in data analysis is data reduction, data display, and conclusion drawing/verification. In Hinduism, hand gestures (mudras) are considered sacred gestures representing various gods and their manifestations. The mudra dewata nawa saṅga in the tradition of pasraman seruling Dewata, Watukaru Bali is unique because it is a combination of hasta mudra and kaya mudra. Mudra dewata nava saṅga is practiced each day differently depending on the deity doing yoga on that day. This mudra dewata nava saṅga is practiced by chanting a stava as the urip (sum of value) of the deity worshiped. Hand gestures in meditation position become a medium for communicating with the gods to balance the vital organs in the body with the universe which is the stana of each god. It is hoped that the theoretical and practical contributions from this qualitative descriptive research on mudra dewata nava saṅga can provide information as a basis for consideration, support, and contributions to yoga practitioners and sadhakas in their routine sadhana. Research on the mudra dewata nava saṅga also needs to be developed by other researchers.